2019
DOI: 10.23939/chcht13.04.451
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenon of Remote Interaction and Sorption Ability of Rare Cross-linked Hydrogels of Polymethacrylic Acid and Poly-4-vinylpyridine in Relation to Erbium Ions

Abstract: 1 Phenomenon of the long-range effect of poly(methacrylic acid) hydrogelpoly(4-vinylpyridine) hydrogel (gPMAA-gP4VP intergel system) оn erbium ions sorption was studied. It was established that the structure of the basic hydrogel had a significant impact on the self-organization of the PMAA hydrogel. The mutual activation of hydrogels was investigated in an aqueous medium. Dependencies of swelling coefficient, specific electric conductivity and pH of aqueous solutions were determined. Individual PMAA and P4VP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
0
13
0
1
Order By: Relevance
“…Our earlier studies [2][3][4][5][6][7][8][9][10][11][12] showed that almost all intergel systems based on acidic (polyacrylic and polymethacrylic acids) and basic (poly-4-vinylpyridine and poly-2-methyl-5-vinylpyridine) rare-crosslinked polymer hydrogels exhibit higher activity than their constituents. Moreover, it was found that the ratio of polymers, at which a high sorption of ions is manifested, differ significantly depending on the nature of acidic and basic hydrogels and the nature of rare earth metals.…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier studies [2][3][4][5][6][7][8][9][10][11][12] showed that almost all intergel systems based on acidic (polyacrylic and polymethacrylic acids) and basic (poly-4-vinylpyridine and poly-2-methyl-5-vinylpyridine) rare-crosslinked polymer hydrogels exhibit higher activity than their constituents. Moreover, it was found that the ratio of polymers, at which a high sorption of ions is manifested, differ significantly depending on the nature of acidic and basic hydrogels and the nature of rare earth metals.…”
Section: Resultsmentioning
confidence: 99%
“…The remote interaction phenomenon [ 29 , 30 , 31 , 32 ] provides a transition of initial macromolecular structures (in the work, ion-exchange resins Amberlite IR120 and AB-17-8) into highly ionized state due to their mutual activation. Activation is a transfer of functional groups from less reactive state to more reactive state and appearance of high ionization and relaxation areas of initial ion exchangers in interpolymer pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the interpolymer system is required to transfer the ion exchangers into a highly ionized state by changing their conformational and electrochemical properties by remote interaction [14]. For activation, the polypropylene meshes with swollen ion exchangers inside (Figure 1a) were placed in a glass with distilled water at a distance of about 1-2 cm opposite each other, forming an interpolymer system "KU-2-8-AV-17-8" (Figure 1b).…”
Section: Activation Of the Interpolymer Systemmentioning
confidence: 99%
“…For the recovery of cerium from industrial solutions, adsorption processes using various materials, such as polymers, activated carbons, or biological materials, have recently sparked increased interest [12][13][14][15]. A common method for cerium ions sorption from solutions can be the use of commercially available and inexpensive ion exchangers: for example, KU-2-8 and AV-17-8 [16][17][18].…”
Section: Introductionmentioning
confidence: 99%